The Analysis of Leadership Expectation Concept for Safety Culture in Company Post Integration Process - Harris, Syafruddin; Arief, N. Nurlela (Borong Newinera Publisher, 2025)
This research aims to explore factor on Leadership Expectation concept for safety culture in company which acquired by holding company through integration process for almost 5 years. This study uses a mixed-method approach, quantitative survey and qualitative semi-structured interview, to obtain a comprehensive understanding of a company's culture following an integration. In the qualitative method, semi-structured interviews were carried out with 6 respondents on managerial level. The Quantitative survey was conducted involving 45 participants representing technician, operators and shift supervisor. The data analysis methodology uses Exploratory Factor Analysis (EFA) to get into stakeholder awareness and understanding of safety behavior. The result revealed above 58% score analysis of five factors shown that employee can demonstrate commitment towards achieving goals, prevent errors and break away from old habits to attain favorable outcomes. The interview feedback show that the respondents believe this cultural journey have an impact to the operational. The main challenge is changing stakeholder behavior and culture that has been embedded from previous times. To overcome the challenges, Leader can provide clear justifications for each safety concern, demonstrate commitment towards achieving goals, offer support to colleagues who take initiative and make decisions, and are open to considering other ideas and perspectives.